Prediction of the margin of victory only from team rankings for regular season games in NCAA men`s basketball - Beaudoin, D.; Duchesne, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
The main objective of this article was to investigate the extent to which the margin of victory can be predicted solely by the rankings of the opposing teams in NCAA Division I men's basketball games. Several past studies have modeled this relationship for the games played during the March Madness tournament. This work aimed at verifying whether the models advocated in previous studies can accurately predict the margin of victory in regular season games. Indeed, most previous articles have shown that a simple quadratic regression model provides fairly accurate predictions of the margin of victory when team rankings only range from 1 to 16. Does that still hold true when team rankings increase to 351? Do the model assumptions hold? Can semi- or nonparametric methods that yield even better results (i.e. predicted margins of victory that more closely resemble actual results) be found? The analyses presented in this article suggest that the answer is "yes" to all three questions!